Shooting Profile of Female Petanque Riau Athletes Judging from Time Effectiveness - Efdi Gusdillah; M. Fransazeli Makorohim (UNIB Press, 2024)
Petanque is a sport that is still developing, so it is understandable that there are still changes to the regulations. By frequently looking for information related to regulations and attending seminars or workshops related to petanque regulations, it is hoped that we can always get the latest information regarding these regulations . This research is an interview and observation technique as well as a literature review technique, aiming to reveal